Gender-based analysis of public speaking anxiety among university students - Nik Fauzi, Sheela Faizura; Morni, Affidah; Ak Joe, Saira; Lendik, Lisbeth Sinan (GADING Journal for the Social Sciences, 2025)
Glossophobia, commonly recognised as the fear of public speaking, is said to surpass even the fear of death for some individuals. Those with acute glossophobia may avoid public speaking opportunities to escape the accompanying surge of adrenaline. Gender differences further complicate the issue, as societal expectations and perceptions can disproportionately impact male and female students’ willingness to participate in public speaking. Using MacIntyre’s Willingness to Communicate (WTC) Model as a framework, this study aims to analyze gender-based differences in students’ perceptions of public speaking and to identify the specific challenges they face while delivering speeches. Thirty undergraduate students, comprising 15 males and 15 females from diploma and bachelor’s degree programs who participated in a public speaking competition at a public university, were included in the study. Convenience sampling was used to select the respondents, and data were collected through a questionnaire adopted from recent studies on public speaking. While most students display a positive outlook and interest in public speaking, gender-specific challenges are evident. Female students report lower situational confidence and readiness to communicate, as reflected by only 40% (6 out of 15) strongly agreeing on the benefits of preparation and practice, compared to 46.7% (7 out of 15) of males, despite exhibiting higher motivation, with 46.7% (7 out of 15) strongly agreeing on their motivation and interest in public speaking, compared to 40% (6 out of 15) of males. The findings highlight the need for tailored, gender-sensitive program improvements that consider the factors influencing students’ willingness to communicate. Strategies such as gender-specific confidence-building workshops, personalised coaching, and interventions targeting societal perceptions and cultural expectations are recommended. These insights provide a foundation for addressing gender disparities in public speaking anxiety future programmes.